The Correlation Between Lower Limb Power and Balance On Roundhouse Kick In Pencak Silat At SMP Negeri 1 Pardasuka - Ismail Nur Hidayat; Joan Siswoyo; Riyan Jaya Sumantri; Candra Kurniawan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the correlation between lower limb power, balance, and roundhouse kick ability in students participating in the extracurricular Pencak Silat program at SMP Negeri 1 Pardasuka. A quantitative approach with a correlational design was used. The sample consisted of 31 students selected through purposive sampling. Data were collected through physical tests to measure lower limb power and balance, as well as an assessment of roundhouse kick ability. The results showed that lower limb power has a significant correlation with roundhouse kick ability (r = 0.582), with a coefficient of determination of 33.9%. Balance also showed a significant correlation with roundhouse kick ability (r = 0.514), with a coefficient of determination of 26.4%. Furthermore, the combination of lower limb power and balance provided a greater contribution to roundhouse kick ability, with a multiple correlation of 0.656 and a coefficient of determination of 43.0%. Based on these findings, it is recommended that the extracurricular Pencak Silat training program focus on improving lower limb power and balance to enhance students' roundhouse kick technique.